Pola hubungan keuangan pemerintah pusat daerah serta pengaruhnya terhadap pertumbuhan ekonomi Provinsi di Indonesia - Rahmadi, Selamet; Hastuti, Dwi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
The research aims to analyze economic growth and the degree of fiscal decentralization (DDF) and measure the influence of the pattern of central-regional government financial relations from the degree of fiscal decentralization (DDF) on the economic growth of each province in Indonesia. The research method uses the Field Research method with secondary data in the form of a time series for 2005-2020. Data comes from the Indonesian Provincial Central Statistics Agency and the Directorate General of Financial Balance of the Republic of Indonesia. The analysis uses quantitative descriptive methods and simple regression methods. The research results concluded that during 2005-2020, provinces in Indonesia experienced an increase in average economic growth. DDF on average falls into the low category with a consultative relationship pattern and has varying influences, namely positive/negative and significant/not significant on economic growth.